(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The goal of this article is to assess the level of harmonization of the laws of Bosnia and Herzegovina with the acquis communautaire in the field of protection from discrimination, to underline the significance of the implementation of European standards even before formal membership in the Union, to identify challenges in interpretation of individual norms of the European law in the context of domestic legal culture and to exemplify or illustrate potential discord between national and European legislation. Having in mind that the enlargement is one of the most important policies of the European Union, scientific analysis can assist candidate countries to successfully harmonize their legislative framework in the field of protection from discrimination with acquis communautaire. Additionally, elaboration and exemplification of the foreign legal concepts can help formulate adequate anti-discrimination policies, containing measures aimed at promotion of principle of genuine equality between groups that enjoy special protection. In assessing the level and success of harmonization of Bosnian legislation with the anti-discrimination laws of the European Union, authors resorted to normative, comparative and analytical method related to the content and scope of application of the anti-discrimination clauses of founding treaties and anti-discrimination directives while using case studies of the Court of Justice of the European Union. It is demonstrated that the divided jurisdiction between different levels of government, plurality of legal systems and complex administrative structure established by the Dayton Peace Agreement represent some of the key procedural challenges in the process of European integration of Bosnia and Herzegovina. It can equally be observed that no other country, candidate for membership in European Union, had to face such internal challenges, amplified by the fact that deep divisions persist after the armed conflict and still found their way into the current political constellation. Concrete substantive challenges Bosnia and Herzegovina is facing when transposing European law are identified in the field of the general exemptions from the principle of equal treatment, the definition of indirect discrimination, wording of the threshold for the burden of proof, exemptions from prohibition of unequal treatment for protection of family relations and awarding damages.